COPYRIGHT LAW AND THE DIGITAL ERA ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This thesis provides a lot of information about copyright and the statement of copyright in the digital age. In addition, digital copyright is foreign specific features of reforms in the states and national Intellectual property law for the social media era adequately explores existing legal issues in modernization.